Hubungan Status Fisik Pra Anestesi Dengan Waktu Pulih Sadar Pasien Post Operasi Dengan General Anesthesia - Hamarno, Rudi; Arif, Taufan; Arifaen, Aditya Mauludin Afkar Nur Arij; Ciptaningtyas, Maria diah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Introduction: The duration of recovery of consciousness in postoperative patients with general anesthesia is a common problem after the patient is transferred to the recovery room. The recovery period of patients after surgery and general anesthesia is influenced by several factors, one of which is the physical condition before anesthesia based on ASA status. The purpose of this study was to determine the relationship between ASA status and the recovery time of patients after surgery with general anesthesia in the recovery room. Method: The study design used a